2013
DOI: 10.1039/c3tb20079e
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanomagnets for effective extraction and sensitive mass spectrometric detection of pathogenic bacterial endotoxin from human urine

Abstract: Title: Chitosan nanomagnets for eff ective extraction and sensitive mass spectrometric detection of pathogenic bacterial endotoxin from human urineThis work demonstrates the technology for the recovery of trace levels of endotoxin from urine samples and their detection using MALDI-MS. CuFeO 2 @chitosan nanomagnets showed 250 times more sensitivity compared to MALDI-MS conventional technique for separation and detection of endotoxin from urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 77 publications
0
45
0
Order By: Relevance
“…Selection of the optimal functionalization mode of MNPs is the most important parameter in MSPE and different types were assayed, including oleic acid , polystyrene , polyaniline , polypyrrole , chitosan , (3‐aminopropyl)triethoxysilane , and polydopamine .…”
Section: Resultsmentioning
confidence: 99%
“…Selection of the optimal functionalization mode of MNPs is the most important parameter in MSPE and different types were assayed, including oleic acid , polystyrene , polyaniline , polypyrrole , chitosan , (3‐aminopropyl)triethoxysilane , and polydopamine .…”
Section: Resultsmentioning
confidence: 99%
“…The Fe 3 O 4 @chitosan nanomagnet approach gave 67× higher sensitivity at 450 mg mL −1 (2.25 mg, 5 mL) compared to the direct MALDI‐MS analysis. CuFeO 2 @chitosan nanomagnets appeared to be about 4× more effective than Fe 3 O 4 @chitosan nanomagnets and 250× more sensitive than the direct MALDI approach (Gopal et al, ).…”
Section: Studies On Specific Carbohydrate Typesmentioning
confidence: 99%
“…Evidently, these results confirmed that the NP-based MALDI-MS can be used in complementary enrichment platforms to increase and to expand the library of protein peaks in bacteria species, which is useful in profiling bacterial species from clinical samples. Furthermore, Fe 3 O 4 -chitosan and CuFeO 2 -chitosan NMs were used as affinity probes for preconcentration and enrichment of trace-level endotoxins (lipopolysaccharides) from human-urine samples [121]. It was observed that the Fe 3 O 4 -chitosan NMs exhibited 67 times higher sensitivity (2.25 μg, 5 μL) compared to direct MALDI-MS analysis.…”
Section: Nanomaterials-based Maldi-ms For Bacterial Identification Anmentioning
confidence: 97%